Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve for x
3 (x – 4) = 12x


Sagot :

Answer:

X  =  [tex]\frac{-4}{3}[/tex]

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

3(x−4)=12x

(3)(x)+(3)(−4)=12x(Distribute)

3x+−12=12x

3x−12=12x

Step 2: Subtract 12x from both sides.

3x−12−12x=12x−12x

−9x−12=0

Step 3: Add 12 to both sides.

−9x−12+12=0+12

−9x=12

Step 4: Divide both sides by -9

[tex]\frac{-9x}{-9} =\frac{12}{9}[/tex]

X [tex]=\frac{-4}{3}[/tex]

Answer:

[tex]=\frac{-4}{3}[/tex]